Trigeminal Neuralgia Associated With a Solitary Pontine Lesion: A Case Report. (January 2022) - Plantone, Domenico; Distaso, Eugenio; D'Onghia, Mariangela; Dell'Aquila, Claudia; Giannini, Antonio; Rinaldi, Giuseppe
Trigeminal neuralgia associated with brainstem lesions is currently considered as a rare condition and only few patients have been reported so far in literature. Tohyama and colleagues recently proposed the nosological entity of trigeminal neuralgia associated with solitary pontine lesion, trying to categorize it as a new clinical syndrome on its own. Based on this description, trigeminal neuralgia associated with solitary pontine lesion patients have an identical clinical presentation compared to other patients with trigeminal neuralgia but have a solitary pontine lesion. The nature of the pontine lesion has been attributed to several etiologies, including ischemia, demyelination or previous pontine viral neuritis. In those patients with a putative demyelinating lesion, a definite diagnosis of multiple sclerosis cannot be made due to the lack of dissemination in space. Very little is known in relation to the cerebrospinal fluid characteristics of this population of patients. We present a case of a 42-year-old man suffering of trigeminal neuralgia associated with solitary pontine lesion with a possible demyelinating etiology. The patient herein described had an atypical trigeminal neuralgia associated with a single pontine lesion. The MRI characteristics of the lesion, along with the presence of oligoclonal bands in the cerebrospinal fluid, suggested a demyelinating etiology. Trigeminal neuralgia associated with a solitary pontine lesion may be categorized as a possible manifestation of solitary sclerosis. Future research need to reveal which features can predict the risk of conversion to clinically defined multiple sclerosis and which treatments modify this risk.